Audit and Coaching Finance : The Role of Auditors as MSME Consultant - Nur Aliah; Miftha Rizkina; Tengku Eka Susilawaty; Nuratikah Nasution (JOURNAL INTELEKTUAL, 2025)
Introduction/Objective: This study aims to explore the role of auditors in providing financial guidance to MSMEs, especially how auditors carry out a consultative role in improving the financial understanding and practices of micro-entrepreneurs. Background of the Problem: MSMEs often face obstacles in terms of financial management, low financial literacy, and non-standardized business records. Novelty: Auditors are not only financial examiners, but also strategic partners of MSMEs in accounting education, digital transformation, and strengthening managerial capacity. Research Method: This study uses a qualitative approach with a case study method, involving in-depth interviews with auditors who have provided guidance to MSMEs such as Lily Kitchen, Unocraft, and Kreasi Ummi Banu. Findings/Results: Auditors play an active role in assisting MSMEs in preparing simple bookkeeping, understanding the principle of separating personal and business finances, and introducing digital record keeping and managing business legality. MSMEs generally show an open and cooperative attitude towards the guidance provided. Conclusion: This study concludes that the role of auditors as financial consultants can be an effective strategy in empowering MSMEs, as long as it is carried out professionally, ethically, and contextually according to the needs of business actors